Management of non-cirrhotic variceal bleeding in pregnant women with Budd-Chiari syndrome in the early second trimester: A case report - Abubakar, Azzaki; Yusuf, Fauzi; Maghfirah, Desi; Kurniawan, Kurniawan; Ezigbo, Eyiuche D. (Narra Sains Indonesia, 2024)
Budd–Chiari syndrome is one of the post-hepatic causes of portal hypertension and a potential obstruction causes liver fibrosis. In pregnancy, obstruction of hepatic veins could occur due to stenosis or thrombosis. Variceal bleeding is the most fatal complication in pregnancy with co-existing Budd–Chiari syndrome, with 29.4% incidence of abortion and 33.3% perinatal mortality. The aim of this case report was to present the management of non-cirrhotic variceal bleeding in pregnant women with Budd–Chiari syndrome in the early second trimester. We report a pregnant female at 13−14 weeks gestation presented to the hospital with profuse hematemesis. Doppler ultrasonography (USG) was utilized to confirm the diagnosis of Budd–Chiari syndrome-hepatic vein occlusion type in pregnancy. Abdominal USG revealed hepatomegaly with hepatic veins dilation, while endoscopy showed grade IV esophageal varices and grade IV gastric varices. Laboratory results indicated disseminated intravascular coagulation due to hemorrhage. The patient was given strict fluid resuscitation and three packed red cells transfusion to stabilize the hemodynamic. Bleeding was successfully managed by intravenous octreotide, tranexamic acid, and vitamin K. The case highlights that the management of non-cirrhotic variceal bleeding in pregnancy with Budd–Chiari syndrome requires a multidisciplinary approach and regular fetal monitoring to ensure optimal outcomes.